Simultaneous occurrence of noma in identical twin brothers: Possibility of a genetic basis - Mujtaba Bala; Ramat Oyebunmi Braimah; Abubakar Abdullahi Bello; Abdurrazaq Olanrewaju Taiwo; Ibrahim Kayode Suleiman (Wolters Kluwer Medknow Publications, 2023)
Background: Noma is a devastating orofacial gangrenous condition that may cause significant mutilation of the facial anatomy. The pathogenesis is poorly understood and has been reported in a setting of low socioeconomic and unhygienic conditions with associated malnutrition. We present this condition in identical twin brothers. Clinical Description: Two identical twin brothers presented with painful swelling of the cheek with ulcerative defects in their upper lips. Both belonged to an impoverished family, and were malnourished, unimmunized, with poor oral hygiene. The typical anatomical presentation of the lesions with the characteristic family setting made the diagnosis consistent with noma (cancrum oris). Other siblings living in the same family with similar background conditions were unaffected. Management: After clinical stabilization, definitive surgical care, including debridement and regular dressings was done under the cover of intravenous antibiotics. With aggressive management along with nutritional rehabilitation and oro-muscular physiotherapy, the acute phase subsided and the patients were discharged in the scarring phase, with a plan for surgical reconstruction of the defect at a later date. Conclusions: The simultaneous presentation of noma in identical twins, with the sparing of other siblings living in the same contributing circumstances, raises suspicion of a genetic basis for this condition, which is as yet unknown. As the etiopathogenesis of noma is evolving, further evidence is needed to establish a genetic predisposition.